IoT-Based Fertiliser Mixing for Precision Farming - Sri Tulasi Ram Rajalingam; Muhammad Muzakkir Mohd Nadzri; Afandi Ahmad; Mohamad Khairi Ishak (International Journal of Integrated Engineering, 2026)
This paper describes the development and evaluation of a prototype fertiliser-mixing system for hydroponic systems based on precision farming, using the Internet of Things (IoT). The system improves nutrient management by controlling fertiliser volume and monitoring real-time concentrations in parts per million (ppm). Multiple sensors were used to provide precise data for nutrient delivery optimisation, including flow, water-level, and total dissolved solids (TDS) measurements. The Blynk IoT platform allows users to input crop-specific fertiliser ratios via a mobile application. While flow sensors maintained accuracy over 94% across 250–1,000 ml target volumes, experimental evaluations revealed that the TDS sensor reached up to 99.6% accuracy within the 100–1,000 ppm range. The average response time from user command to system action was 22.17 seconds, and the system adjusted fertiliser concentrations to within 92.8–98.8% of target ppm levels. According to these findings, the prototype consistently maintains appropriate nutrient levels, with slight variation, enabling prompt adjustments and ensuring optimal growing conditions in hydroponic farming.